Edukasi Hukum Digital sebagai Upaya Pencegahan Penyalahgunaan Media Sosial di Kalangan Mahasiswa Universitas Teknologi Mataram (UTM) - Jamaludin; Tata Eliestiana Dyah A (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The misuse of social media in Indonesia has become an increasingly concerning issue, particularly among teenagers and university students who lack awareness of the legal consequences of digital activities. Students at Universitas Teknologi Mataram (UTM), as active social media users, are vulnerable to committing violations, whether consciously or unconsciously, due to limited understanding of the Information and Electronic Transactions Law (UU ITE). To address this, digital law literacy is necessary to help students become more aware of existing legal boundaries and to encourage them to use social media as a positive tool for self-development and academic purposes. This community service program was designed to provide digital law education as a preventive measure against social media misuse among students. The methods employed included interactive socialization through lectures, discussions, case studies, and the distribution of legal literacy materials such as leaflets and infographics. The results showed an improvement in students’ understanding of the importance of ethics, legal compliance, and the risks of digital misconduct, including hate speech, hoax dissemination, and other online violations. The program also introduced the latest provisions of Law No. 1 of 2024 concerning the amendment of Law No. 11 of 2008 on Information and Electronic Transactions (UU ITE). Overall, this activity highlights the importance of continuous digital law education to encourage UTM students to be wiser, more critical, and responsible in their use of social media.